Recent Progress in Andrographolide Derivatization: Structural Modification and Biological Activity - Wang, Wang; Yang, Yueying; Liu, Yang; Sun, Dejuan; Li, Hua; Chen, Lixia (Mini Reviews in Medicinal Chemistry, 2022)
Natural products have remarkable structural diversity and biological characteristics, providing researchers with more possibilities to develop novel drugs for disease therapeutics. Andrographolide, an ent-labdane diterpenoid from traditional Chinese medicines, Andrographis paniculata, exhibits a broad range of biological activities, which has been a hot area of research for several years. Up to now, lots of its derivatives with multiple bioactivities have been prepared through chemical modification. This review summarizes andrographolide derivatives prepared in the last ten years (2006-present), classifies them by different biological activities, and provides some discussion about the design of novel and potent derivatives.
Keywords: bioactivity